The Neurostimulation Appropriateness Consensus Committee (NACC): Recommendations on Bleeding and Coagulation Management in Neurostimulation Devices. Issue 1 (2nd January 2017) - Deer, Timothy R.; Narouze, Samer; Provenzano, David A.; Pope, Jason E.; Falowski, Steven M.; Russo, Marc A.; Benzon, Honorio; Slavin, Konstantin; Pilitsis, Julie G.; Alo, Kenneth; Carlson, Jonathan D.; McRoberts, Porter; et al.
Abstract : Introduction: The Neurostimulation Appropriateness Consensus Committee (NACC) was formed by the International Neuromodulation Society (INS) in 2012 to evaluate the evidence to reduce the risk of complications and improve the efficacy of neurostimulation. The first series of papers, published in 2014, focused on the general principles of appropriate practice in the surgical implantation of neurostimulation devices. The NACC was reconvened in 2014 to address specific patient care issues, including bleeding and coagulation. Methods: The INS strives to improve patient care in an evidence‐based fashion. The NACC members were appointed or recruited by the INS leadership for diverse expertise, including international clinical expertise in many areas of neurostimulation, evidence evaluation, and publication. The group developed best practices based on peer‐reviewed evidence and, in the absence of specific evidence, on expert opinion. Recommendations were based on international evidence in accordance with guideline creation. Conclusions: The NACC has recommended specific measures to reduce the risk of bleeding and neurological injury secondary to impairment of coagulation in the setting of implantable neurostimulation devices in the spine, brain, and periphery.